肩関節周囲炎後例における肩峰骨頭間距離と肩関節可動域制限の関連についての検討 - 井上 宜充; 岡本 賢太郎; 久合田 浩幸; 川 桃子; 荒井 哉美; 安保 麻美; 田村 拓也; 山本 和良 (理学療法学, 2010)
Purpose: The acromiohumeral interval (AHI) is an index used for the diagnosis of rotator cuff tear. We measured the AHI in subjects with shoulder pain with limited range of motion of the shoulder joint, and examined the correlation between AHI and limited range of motion of the shoulder joint to examine the effectiveness of AHI measurement in patients with scapulohumeral periarthritis. Method: Fifteen shoulders of 15 patients in whom the contralateral shoulder joint was on the healthy side who were underwent treatment for scapulohumeral periarthritis participated in the study. The range of motion of both shoulders, the AHI from the frontal view of the shoulder joint, and the ratio of AHI to the caput humeri maximum diameter (A/H ratio) were examined, and the correlation of the range of motion of the shoulder joint and AHI・A/H ratio were examined (p < 0.05). Results: As a result of measuring the AHI of the shoulder joint of the affected side, the AHI was 9.6 ± 2.6 mm. There was the negative correlation between A/H ratio of the affected side and differences of flexion and abduction angles in healthy and affected shoulder joint. Conclusions: Between the subacromial surface and the caput lies the second shoulder joint and, when elevating the upper extremity, the caput humeri must passes under the lower part of the acromion. The AHI is equal to the measurement of the fissure distance of the upper portion of the second shoulder joint, and we thought that for obtaining normal ranges of motion in patients with scapulohumeral periarthritis, a sufficiently wide AHI is required to incorporate the caput humeri. This study suggested functional meaning for A/H ratio determination in patients with scapulohumeral periarthritis. 【目的】肩峰骨頭間距離（AHI）は，腱板断裂の診断のために使用される指標である。我々は，肩関節周囲炎後に肩関節痛と関節可動域制限をきたした症例におけるAHI測定の有効性を検討するために，AHIを測定し，AHIと肩関節可動域制限との関連について検討をした。【方法】対象は肩関節周囲炎発症後に肩関節可動域制限を呈し治療中の症例で，片側羅患例15例15肩であった。対象の両肩関節可動域と，肩関節X線正面像からAHIとAHIの上腕骨頭最大径比（A/H比）を測定し，肩関節可動域とAHI・A/H比の相関関係を検討した（p < 0.05）。【結果】対象の患側肩関節におけるAHIを測定した結果，AHIは9.6 ± 2.6 mmであった。また，患側A/H比と肩関節屈曲・外転角度健患差との間に負の相関を認めた。【結論】肩峰下面と骨頭間には第2肩関節が存在し，上肢の挙上動作時には，上腕骨頭が肩峰の下方に取り込まれる必要がある。AHIは第2肩関節の上方部分の裂隙距離を測定するに等しく，正常可動域を獲得するためには，上腕骨頭を取り込むための十分なAHIの広さが必要であると考えた。今回の研究から，肩関節周囲炎発症後に関節可動域制限を呈した症例ではA/H比測定には機能的意義があることが示唆された。